2000
DOI: 10.1094/pdis.2000.84.10.1085
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Transmission and Spread of Sugarcane yellow leaf virus

Abstract: Sugarcane, Saccharum spp. hybrid, is widely infected in the United States and many other countries with a yellowing and stunting disease called sugarcane yellow leaf syndrome. The causal agent, Sugarcane yellow leaf virus (ScYLV), is a Polerovirus of the Luteoviridae family. In this study, it was transmitted by the sugarcane aphid, Melanaphis sacchari, and also by the corn leaf aphid, Rhopalosiphum maidis, and the rice root aphid, R. rufiabdominalis. Two other aphids that infest sugarcane in Hawaii did not tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
90
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(94 citation statements)
references
References 11 publications
3
90
1
Order By: Relevance
“…Accessions T3, T4, and T5 (not listed) functioned as negative controls and represent plants independently generated via meristem culture from the T6 accession via previously described methods (46). Numerous anecdotal reports suggest that SCYLV is probably distributed worldwide.…”
Section: Resultsmentioning
confidence: 99%
“…Accessions T3, T4, and T5 (not listed) functioned as negative controls and represent plants independently generated via meristem culture from the T6 accession via previously described methods (46). Numerous anecdotal reports suggest that SCYLV is probably distributed worldwide.…”
Section: Resultsmentioning
confidence: 99%
“…Rassaby et al [14] reported virus-free susceptible cultivar planted near SCYLVinfected sugarcane resulted in 45 % of infection after 4 months. Schenck and Lehrer [17] reported that R. maidis can transmit SCYLV from sugarcane to cereal grasses. Apart from sugarcane, the other crops such as barley, oats and wheat are susceptible to SCYLV.…”
Section: Discussionmentioning
confidence: 99%
“…Long range SCYLV transmission in sugarcane is achieved through infected seed canes and secondarily by aphids in a persistent manner [14]. Earlier, Schenck and Lehrer [17] reported three aphid species namely Melanaphis sacchari (sugarcane aphid), Rhopalosiphum maidis (corn leaf aphid) and R. rufiabdominalis (rice root aphid) as vectors of SCYLV in Hawaii. However, later studies revealed that, among them, M. sacchari was the only important vector in Hawaii.…”
Section: Introductionmentioning
confidence: 99%
“…However, the seed multiplication rate is too low (1:6 to1:8) which makes the spread of newly released varieties slow, taking over 10 years to scale up a newly released variety to the commercial level (Sengar, 2010;Cheema and Hussain, 2004), and also it facilitates the spread of pathogens and may result in epidemics (Schenck and Lehrer, 2000). Moreover, the method requires large nursery space: one hectare nursery for 10 to 15 hectares field planting (Sundara, 2000).…”
Section: Challenges Facing Sugarcane Production In Kenyamentioning
confidence: 99%